Answer:
The new force becomes (1/9)th of the original force.
Step-by-step explanation:
The gravitational force between two masses is given by :
![F=G(m_1m_2)/(r^2)](https://img.qammunity.org/2022/formulas/biology/high-school/xyp7hvpgabjvvytso444yesdubngw904fc.png)
Where
r is the distance between masses,
If the new distance is, r' = 3r
The new force is given by :
![F'=G(m_1m_2)/(r'^2)\\\\F'=G(m_1m_2)/((3r)^2)\\\\F'=(1)/(9)* G(m_1m_2)/(r^2)\\\\F'=(F)/(9)](https://img.qammunity.org/2022/formulas/physics/college/vz7r3jsncggyk1e0zqctv1tucx2qymrs7i.png)
So, the new force becomes (1/9)th of the original force.